Lessons from the Nile Basin Development Challenge Program: An Institutional History - Merrey, Douglas J.; Swaans, Cornelis P.M.; Le Borgne, Ewen (CGIAR Challenge Program on Water and Food, 2013)
The Nile Basin Development Challenge (NBDC) program is a multi-disciplinary, multi-institutional participatory “Research for Development” (R4D) partnership. It is aimed at improving the resilience of rural livelihoods in the Ethiopian highlands through a landscape approach to rainwater management (RWM), with a special focus on the Blue Nile (Abay) River Basin. The R4D paradigm has several elements, including: using scientific research as a means to achieve specific development goals rather than as an end in itself; a focus on achieving tangible systemic changes over the long run; the use of a transparent model or “theory of change” to guide the program; inclusive partnerships among all participants based on mutual respect; and, a strong emphasis on collectively learning from experience and sharing that experience more widely. The NBDC uses multiple means to learn lessons from its experience as a basis for adapting its activities. This Institutional History consolidates and communicates some of those lessons.